Association between physical activity and costs in very mild to moderately frail community-dwelling older adults: a cross-sectional study - Sophie Gottschalk; Hans-Helmut König; Christian Werner; Tim Fleiner; Christian Thiel; Gisela Büchele; Martina Schäufele; Kilian Rapp; Judith Dams (BMC, 2024)
Abstract Background Physical activity (PA) plays a vital role in maintaining the functional ability that enables well-being in older age (healthy aging), potentially also saving costs for the healthcare system and society. The aim of this study was to examine the association between PA and healthcare and societal costs in a sample of very mild to moderately frail older adults. Methods This cross-sectional study is a secondary analysis using baseline data from the PromeTheus randomized-controlled trial, which included 385 very mild to moderately frail community-dwelling older adults (70 + years) from Germany. Participants self-reported their health-related resource use in the previous 6 months (FIMA questionnaire), which was monetarily valued using standardized unit costs. PA was also self-reported using the German Physical Activity Questionnaire for middle-aged and older adults (German-PAQ-50+) and categorized as 'insufficient'/'sufficient' or 'insufficient'/'moderate'/'high' in accordance with the World Health Organization guidelines for PA. Mean and median healthcare costs (including outpatient, inpatient, rehabilitation, formal care, and medication costs) and societal costs (healthcare costs plus informal care costs) for different PA groups were estimated using generalized linear models and quantile regression, with sociodemographic variables and physical capacity (Short Physical Performance Battery) as covariates. Results Of the sample, 24% were classified as insufficiently, 23% as moderately, and 54% as highly active. Sufficient PA, especially high PA, was associated with lower costs in the 6 months prior to data collection compared to insufficient PA (-€6,237, 95% CI [-10,656; -1,817] and -€8,333, 95% CI [-12,183; -4,483], respectively). The cost difference between PA intensity groups was largely driven by differences in informal care costs and decreased substantially when physical capacity was accounted for in the analyses; e.g., the mean difference in societal costs between sufficient and insufficient PA decreased from -€7,615 (95% CI [-11,404; -3,825]) to -€4,532 (95% CI [-7,930; -1,133]). Conclusion Promoting PA throughout the lifespan as a means of promoting healthy aging and reducing dependency in old age could potentially provide economic benefits and help to mitigate the economic consequences of an aging population with increasing health and long-term care needs. Future longitudinal studies should attempt to disentangle the mediating and confounding role of physical capacity and health status in the association between PA and costs.